Financial Technology (FinTech) Analysis in Improving Banking Services (Study at BSI KCP Boyolali) - Layla Qodri Ani; Moh. Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2025)
This study aims to explore the role of fintech in improving Islamic banking services at Bank Syariah Indonesia (BSI) Boyolali Sub-Branch Office (KCP), focusing on operational efficiency, financial inclusion, and access to Islamic finance. Through the utilization of technologies such as mobile banking and digital platforms, fintech has successfully accelerated the banking service process, reduced physical interactions, and made it easier for people in remote areas to access financial services. Services such as digital payments, money transfers, and microloans enable people who previously did not have access to traditional bank accounts to participate in the formal financial system. In addition, the use of technology for risk evaluation and Islamic financing also expands opportunities for MSME players in Boyolali to obtain financing that complies with sharia principles. However, it is important for BSI KCP Boyolali to continue improving digital literacy and data security, as well as developing fintech features that are more suited to local needs in order to optimize the potential of fintech in supporting financial inclusion and regional economic growth.